Newly discovered genomic mutation patterns in radiation-induced small intestinal tumors of ApcMin/+ mice. - Daisuke Iizuka; Megumi Sasatani; Atsuko Ishikawa; Kazuhiro Daino; Tokuhisa Hirouchi; Kenji Kamiya (PLoS ONE, 2023)
Among the small intestinal tumors that occur in irradiated mice of the established mouse model B6/B6-Chr18MSM-F1 ApcMin/+, loss of heterozygosity analysis can be utilized to estimate whether a deletion in the wild-type allele containing the Adenomatous polyposis coli (Apc) region (hereafter referred to as Deletion), a duplication in the mutant allele with a nonsense mutation at codon 850 of Apc (Duplication), or no aberration (Unidentified) has occurred. Previous research has revealed that the number of Unidentified tumors tends to increase with the radiation dose. In the present study, we investigated the molecular mechanisms underlying the development of an Unidentified tumor type in response to radiation exposure. The mRNA expression levels of Apc were significantly lower in Unidentified tumors than in normal tissues. We focused on epigenetic suppression as the mechanism underlying this decreased expression; however, hypermethylation of the Apc promoter region was not observed. To investigate whether deletions occur that cannot be captured by loss of heterozygosity analysis, we analyzed chromosome 18 using a customized array comparative genomic hybridization approach designed to detect copy-number changes in chromosome 18. However, the copy number of the Apc region was not altered in Unidentified tumors. Finally, gene mutation analysis of the Apc region using next-generation sequencing suggested the existence of a small deletion (approximately 3.5 kbp) in an Unidentified tumor from a mouse in the irradiated group. Furthermore, nonsense and frameshift mutations in Apc were found in approximately 30% of the Unidentified tumors analyzed. These results suggest that radiation-induced Unidentified tumors arise mainly due to decreased Apc expression of an unknown regulatory mechanism that does not depend on promoter hypermethylation, and that some tumors may result from nonsense mutations which are as-yet undefined point mutations.